"Better never means better for everyone": White feminist necropolitics and Hulu's The Handmaid's Tale. Issue 1 (2nd January 2023) - Neville-Shepard, Meredith
ABSTRACT: This article builds on those who have critiqued Hulu's The Handmaid's Tale along racial lines and calls into question the esteemed status the show holds as a rhetorical resource for contemporary feminist activism. By drawing attention to the parasitical relationship that the archetype of the vulnerable (but resilient) white woman has to Black pain and death, I argue that the series further calcifies the dominance of white feminism, enacting what I term "white feminist necropolitics." To illuminate this theory, the essay presents a close analysis of The Handmaid's Tale . Specifically, I demonstrate how the show deploys post-racial logics to center a white feminist heroine whose story of saviorism relies on the cooptation of Black pain and the exploitation of Black death. Ultimately, this critical reading of the series points to the ways in which white feminism and necropolitics are intricately entangled.